Reverse transfer of corporate social responsibility practices from brazilian subsidiaries of multinationals - Felipe Mendes Borini; Moacir de Miranda Oliveira Júnior; Gabriel Vouga Chueke (BBR: Brazilian Business Review)
The theme of corporate social responsibility (CSR) has not been widely examined in the context of multinationals. This dearth is even greater with respect to subsidiaries, particularly the subject of reverse transfer of practices, that is, the transfer of practices developed in subsidiaries back to the parent company. Because of this theoretical gap, the present article investigates the factors involved on reverse transfer of CSR practices. The research hypotheses test the importance of developing nonlocation-bound capabilities, of integration between subsidiaries and parent and of institutional distance. The data were obtained by a survey of the main foreign subsidiaries in Brazil. All told, we analyzed 150 Brazilian subsidiaries of multinationals, by applying multiple linear regression. The results indicate that the reverse transfer of CSR depends on the development of nonlocation-bound capabilities of the subsidiaries and integration between the parent company and its foreign subsidiaries.